2016
DOI: 10.1002/adma.201603428
|View full text |Cite
|
Sign up to set email alerts
|

Fast Growth and Broad Applications of 25‐Inch Uniform Graphene Glass

Abstract: A unique ethanol-precursor-based LPCVD route is developed for the fast (4 min, improved 20 times) and scalable (25 inch, improved six times) growth of high-quality graphene glass. The obtained graphene glass presents high uniformity across large areas and is demonstrated to be an excellent material for constructing switchable windows and biosensor devices, owing to its excellent transparency and conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 48 publications
1
92
0
2
Order By: Relevance
“…Chen et al [26] compared the performance of graphene glass-based sensors (detection limit 0.1 μg/mL, response 0.1 V), using a commercial SPR sensor to detect the anti-IgG. They showed that a detection of 0.625 μg/mL was difficult to achieve for a commercial SPR sensor (angle-modified sensor).…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [26] compared the performance of graphene glass-based sensors (detection limit 0.1 μg/mL, response 0.1 V), using a commercial SPR sensor to detect the anti-IgG. They showed that a detection of 0.625 μg/mL was difficult to achieve for a commercial SPR sensor (angle-modified sensor).…”
Section: Resultsmentioning
confidence: 99%
“…As for the growth of graphene, gaseous hydrocarbons including methane (CH 4 ) and ethane (C 2 H 6 ) have been reported to be utilized in the CVD process, and CH 4 is the most widely used precursors. Benzene (C 6 H 6 ), toluene (C 6 H 5 CH 3 ), and ethanol (C 2 H 5 OH) have also been chosen for graphene growth as liquid carbon sources. C 6 H 6 and C 6 H 5 CH 3 own relatively low decomposition temperature and are suitable for the low‐temperature growth, while ethanol is low cost and nontoxic.…”
Section: Vapor‐phase Growth Of High‐quality Wafer‐scale 2d Materialsmentioning
confidence: 99%
“…The past decade has witnessed various breakthroughs in two‐dimensional (2D) materials . Academia and industry have paid tremendous attention and high expectations on 2D materials, as they have broad prospects in various fields owing to their remarkable and tunable physical and chemical properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, metals or dielectric materials, such as copper [222,223], nickel [224], quartz or glass [225,226], are often served as the templates for growth of graphene films. Copper foils and meshes (Fig.…”
Section: Science China Materialsmentioning
confidence: 99%